Market orientation, service quality and organizational performance in service organizations in Malaysia - T., Ramayah; Nusrah, Samat; Lo, May-Chiun (Emerald Group Publishing Limited, 2011)
Purpose – This study seeks to examine the relationship between market orientation, service quality, and their impact towards organizational performance. Design/methodology/approach – A total of 175 sets of structured questionnaires were distributed to managers of 175 service organizations in the northern region of Malaysia, and only 57.71 percent of it, which is 101, was returned. Findings – The results show that market orientation has a significant effect on organizational performance and service quality. Also, service quality has a significant effect on organizational performance. Interestingly, this study found that service quality partially mediates the relationship between market orientation and organizational performance. Research limitations/implications – In order to be more generalized to the service industry, a wider sample with multiple responses from different individuals and management levels can be used for any future study. The same study can also be done by including other mediating or even moderating variables. Practical implications – There is still a shortage of research studying the impact of service quality as a mediator on the relationship between market orientation and organizational performance. Thus, this study contributes a significant knowledge to the service industry. Originality/value – This study adds to the literature by bridging the gap and showing the importance of market orientation in service organizations. It also provides some theoretical contributions to the development of market orientation in relation to service quality and organizational performance.